Production of xylooligosaccharides from lignocellulosic biomass using enzymatic hydrolysis - Nurul Aishah, Mazlan (2020)
Xylooligosaccharides (XOS) has become the center of attention among researchers recently due to its properties that possess the prebiotic effect. The industrial XOS production mainly relies on starch as source of xylan. Nevertheless, the sustainability production of XOS from commodity crop has been disputed since it triggers the increment of XOS market price due to the scarcity of raw material supply which mainly came from corncob. Corresponding to this, lignocellulosic biomass is notified as the best candidate to substitute commodity crop as raw material in XOS production since this material has been proven having high xylan content that can be converted into other value-added chemicals. This present study used three types of lignocellulosic biomass namely oil palm frond bagasse (OPFB), oil palm empty fruit bunch (OPEFB) and rice straw (RS) for XOS production via enzymatic hydrolysis using commercial Cellic Htec2 enzyme. At the beginning of this study, all raw materials were screened in terms of compositions to select the best material for XOS production. For this purpose, fixed pretreatment condition was employed where the solid was soaked in 0.1% nitric acid (NHO3) with 10% solid loading in water bath with temperature maintained at 60 ℃ for 12 h and revealed that OPFB was the best candidate for XOS production due to the highest enhancement of xylan yield and lignin removal after pretreatment. The pretreatment conditions of OPFB then studied via response surface methodology (RSM) where temperature, time, acid concentration, agitation and substrate loading were evaluated during screening, whilst temperature and acid concentration being the selected factors for optimization. The findings indicated that the implementation of nitric acid pretreatment at 42 °C with 0.02% acid has increased the xylan content by about 4% (from 27.63% during screening to 28.74% in optimization). However, lignin content was identified higher at this condition (17.94%) compared to amount of lignin from the screening study (15.03%). RSM was also employed in the enzymatic hydrolysis to achieve the optimum XOS production in which five factors were assess in screening (substrate loading, enzyme dosage, temperature, time and agitation speed) and two most contributed factors from screening study (substrate loading and enzyme dosage) were further analysed in optimization study. From the results, XOS production was increased from 4.43 mg/mL in screening study, to 5.63 mg/mL in optimization study. The maximum XOS acquired during optimization when the sample was reacted with 420 U/mL enzyme dosage using 5% (w/v) solid loading. The performance of enzymatic hydrolysis process in XOS production was investigated using Modified Prout-Tompkins equation. The model reflects the heterogenous behavior of the process through pre-exponential factors that represents the topochemical characteristic which decreased at maximum xylan conversion. This showed that accessibility of active site also decreased at this point. Overall, the finding of this study suggested that application of mild nitric acid pretreatment can improve production of XOS with the involvement of commercial Cellic Htec2 enzyme which consequently reduce the production cost with the usage of this enzyme. This study is important to discover the potential of low-cost agricultural waste for production of value-added product especially XOS that can be useful in food and pharmaceutical industries.